2015
DOI: 10.1038/srep14781
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacologically targeted NMDA receptor antagonism by NitroMemantine for cerebrovascular disease

Abstract: Stroke and vascular dementia are leading causes of morbidity and mortality. Neuroprotective therapies have been proposed but none have proven clinically tolerated and effective. While overstimulation of N-methyl-d-aspartate-type glutamate receptors (NMDARs) is thought to contribute to cerebrovascular insults, the importance of NMDARs in physiological function has made this target, at least in the view of many in ‘Big Pharma,’ ‘undruggable’ for this indication. Here, we describe novel NitroMemantine drugs, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 51 publications
1
64
0
Order By: Relevance
“…No other blockers, apart from nitromemantine, functioning similarly to memantine and having therapeutic prospects have currently been registered67. It is known that NMDA receptors play an important role in the mammalian brain, being involved not only in the brain development and cognitive processes, but also in the development of some acute and chronic neurodegenerative diseases, including stroke, AD, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…No other blockers, apart from nitromemantine, functioning similarly to memantine and having therapeutic prospects have currently been registered67. It is known that NMDA receptors play an important role in the mammalian brain, being involved not only in the brain development and cognitive processes, but also in the development of some acute and chronic neurodegenerative diseases, including stroke, AD, and depression.…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, a NitroMemantine drug can provide increased blockade of hyperactivated NMDARs through S-nitrosylation in addition to channel block, thus affording more neuroprotection that that offered by memantine [15,81] (Figure 3). Consistent with this notion, NitroMemantine protected neurons more efficiently than memantine in cellular and animal models of AD and cerebrovascular disease [15,82]. The lead NitroMemantine candidate developed to date, designated YQW-036/NMI-6979, has shown a favorable pharmacokinetic profile, excellent CNS penetration, and good safety index in early preclinical studies [81,82].…”
Section: Possible Approaches To Pharmacologically Modulate Formation mentioning
confidence: 98%
“…Consistent with this notion, NitroMemantine protected neurons more efficiently than memantine in cellular and animal models of AD and cerebrovascular disease [15,82]. The lead NitroMemantine candidate developed to date, designated YQW-036/NMI-6979, has shown a favorable pharmacokinetic profile, excellent CNS penetration, and good safety index in early preclinical studies [81,82]. The NitroMemantines are currently being evaluated for clinical trials for AD and other neurological disorders.…”
Section: Possible Approaches To Pharmacologically Modulate Formation mentioning
confidence: 99%
“…S-nitrosylation maintains inhibition of the extrasynaptic NMDA receptor even after the remaining memantine moiety dissociates from the modified receptor [reviewed in (Nakamura and Lipton, 2016)]. In a recent report, Takahashi, et al demonstrated that NitroMemantines selectively S-nitrosylated ischemic neurons and in turn reduced brain damage in a rat model of ischemic stroke (Takahashi et al, 2015). Besides…”
Section: Accepted Manuscriptmentioning
confidence: 99%